PENGARUH PARTISIPASI MASYARAKAT, PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMITMEN ORGANISASI TERHADAP PEMBELIAN IMPULSIF DI MEDAN MALL - TOGA SEHAT SIHITE (JURNAL ILMIAH SIMANTEK, 2022)
The development of increasingly sophisticated information technology allows consumers to absorb information about a product or service more easily. Consumers are increasingly selective in choosing products to use or consume at this time so that consumers will give positive responses to products. The purpose of this study is to find out how the influence of community participation, the use of Information Technology and Organizational Commitment has an effect on Impulsive Purchases at Medan Mall. This research was conducted in the city of Medan with multiple linear regression data analysis techniques using the Statistical Package of Social Science (SPSS) version 22.0 for Windows. Determination of the number of samples through non-probability sampling techniques, especially purposive sampling, as many as 150 respondents. It was found that the community participation variable, the use of Information Technology, had a positive and significant effect on impulse buying at Medan Mall and the organizational commitment variable had a positive and significant effect on impulsive buying at Medan Mall.